A review of metasurface-assisted RCS reduction techniques - Murugesan, Akila (2022)
This review discusses the evolution of the various radar cross-section (RCS) reduction techniques, with an emphasis on metasurfaces. The paper first introduces the terms RCS and RCS reduction and then discusses conventional and modern techniques to reduce RCS. The two main strategies used are scattering and absorption. The traditional methods of shaping and Radar Absorbing Material (RAM) are first briefly reviewed, followed by an extensive review of metasurface-based RCS reduction. RCS-reducing metasurfaces have the unique characteristics of acting as scatterers and absorbers. They are also described with regard to their passive and active configurations. The paper discusses RCS reduction techniques with respect to profile, bandwidth, angular stability, polarization sensitivity, design complexity, and cost-effectiveness. A comprehensive comparison chart based on the performance parameters such as bandwidth, size and angular stability is tabulated for the different types of metasurfaces. The review also details areas that require further investigation.